Writing the New World : The Politics of Natural History in the Early Spanish Empire - Caraccioli, Mauro Jose (Book collections on Project MUSE., 2021)
"In this volume, Mauro Caraccioli examines the natural history writings of early Spanish missionaries, using these texts to argue that colonial Latin America was fundamental in the development of modern political thought"--